QUALITATIVE EXPLORATION INTO THE EFFECTIVENESS AND EFFICIENCY OF PUBLIC SERVICE (BUREAUCRACY) IN DEMOCRATIC SOUTH AFRICA: AN ATTEMPT TO FORGE FOR A VIABLE, SUSTAINABLE, LEGITIMATE, AND WORKABLE STRONG PUBLIC BUREAUCRATIC ALTERNATIVE MODEL FOR MZANSI AFRIC - Bogopane, Lebosa Peter (European Scientific Journal, ESJ, 2015)
This article represented an attempt to explore the tension between politics and administration, not only as a bone of contention between the two, but also the negative impact this has in good governance and on the effectiveness, efficiency, sustainability, viability, legitimacy and workability of the public service in the country. In undertaking this exploratory discourse, the author commenced by identifying two pertinent themes that are central to a well performing public bureaucracy, namely (1) politicization /depoliticisation and (2) Professionalisation / unprofessionalisation of the public service (bureaucracy), and used them as the basis for this exploratory study. The writer preferred a qualitative paradigm to the study, and thus employed qualitative data collection and gathering methods (i.e. participant observation, in-depth interviewing, qualitative document study, and qualitative case study), and qualitative data analysis and interpretation techniques (i.e. qualitative content analysis and qualitative case study analysis) to arrive at the anticipated findings, as directed by the key research problem and its sub-problems, the research questions, and the research objectives underpinning the study. Based on these findings, several recommendations were made, that the study believes, will make a meaningful contribution in enhancing and consolidating effectiveness and the efficiency of public service (bureaucracy) in Mzansi Africa (South Africa).